Talent management in higher education: how institutional logic shapes faculty recruitment, development, performance, and identity - Balqis Putri Hidayatullah; Muhammad Yorga Permana (Universitas Muhammadiyah Enrekang, 2025)
This study examines the underlying mechanisms that shape faculty talent management within contrasting higher-education environments in Indonesia. Through a multi–case analysis of a private and a public university, the research identifies five key structural drivers, system formalization, development infrastructure, performance philosophy, career mobility pathways, and identity alignment, that influence faculty motivation, engagement, and retention. The findings reveal that private institutions benefit from highly formalized and resource-rich systems that enhance clarity, capability-building, and accountability, yet may create heightened workload pressure. Conversely, public institutions offer greater autonomy but face challenges related to ambiguity, limited developmental support, fragmented performance evaluation, and constrained career progression. Drawing on these insights, the study proposes an integrated, theory-driven model consisting of four strategic pillars: the Faculty Role Clarity Framework, the Faculty Development Architecture, the Balanced Performance and Recognition Model, and the Faculty Career Mobility & Identity Alignment Framework. Accompanied by empirically justified implementation plans, this model offers a practical roadmap for strengthening faculty experiences across diverse institutional contexts. The study concludes that aligning structural systems with faculty psychological needs and professional identities is essential for fostering sustainable academic excellence and institutional competitiveness in Indonesian higher education.